Seizures, Edema, Thrombosis, and Hemorrhages: An Update Review on the Medical Management of Gliomas - Zoccarato, Marco; Nardetto, Lucia; Basile, Anna Maria; Giometto, Bruno; Zagonel, Vittorina; Lombardi, Giuseppe (Frontiers in Oncology, 2021)
Patients affected with gliomas develop a complex set of clinical manifestations that deeply impact on quality of life and overall survival. Brain tumor-related epilepsy is frequently the first manifestation of gliomas or may occur during the course of disease; the underlying mechanisms have not been fully explained and depend on both patient and tumor factors. Novel treatment options derive from the growing use of third-generation antiepileptic drugs. Vasogenic edema and elevated intracranial pressure cause a considerable burden of symptoms, especially in high-grade glioma, requiring an adequate use of corticosteroids. Patients with gliomas present with an elevated risk of tumor-associated venous thromboembolism whose prophylaxis and treatment are challenging, considering also the availability of new oral anticoagulant drugs. Moreover, intracerebral hemorrhages can complicate the course of the illness both due to tumor-specific characteristics, patient comorbidities, and side effects of antithrombotic and antitumoral therapies. This paper aims to review recent advances in these clinical issues, discussing the medical management of gliomas through an updated literature review.